A Linear Algebraic Approach In Analyzing the M/GE/1 And GE/M/1 Queuing Systems At Equilibrium - bin Mustafa, Mohammad Saleh; bin Othman, Abu Talib (Malaysian Journal of Computer Science, 2017)
Uses the algebraic approach in the queuing theory to derive the M/G/1 equilibrium solution for the number of jobs in the system when the probability distribution function representing the general distribution is the generalized exponential (GE-type). Similarly the GE/M/1 system is solved. Furthermore, it has been shown that as expected the solutions are equivalent to the maximum entropy solutions of the M/G/1 and G/M/1 systems respectively at equilibrium.